Clinico-pathological study of craniopharyngioma - Sikandar, Mohammed; Venugopal, G.; Reddy, M. Srinivas (International Surgery Journal, 2022)
Background: Craniopharyngioma is a tumour of the suprasellar region that histologically has two distinct variants with some differences in clinical behaviour. The papillary type is almost always seen in adults and has a more indolent course. We studied clinical and radiological characteristics, surgical resectability, clinical outcome and recurrence patterns in tertiary care center. Methods: The present study is a prospective study, comprising of 32 patients of craniopharyngiomas studies over a period of 3 years. All the patients were thoroughly evaluated for the symptoms and signs with particular stress on visual impairment and field defects. Results: There were 16 male and 16 female patients. The incidence of craniopharyngioma was observed more in the age group of 6-10 years. Fundoscopy examination revealed optic atrophy and papilloedema in (56.25%) eases. Endocrinological dysfunction were present in 31.25% cases. Appearance on computed tomography (CT) scan showed 31.25% as cystic and 68.75% was mixed respectively. Surgical approach to the tumor was through pterional approach in (75%) sub frontal in (18.75%) transphenoidal in 18.75%. There was 2 death, 10 patients were advised postoperative radiotherapy and follow up period was from 6 months to 2 years. There were 6 recurrences out of 32 patients who were under follow-up. Conclusions: Treatment should focus not only on long term control and survival, but also on the reduction of the disease and related morbidity and preservation of quality of life.